Gallery Walk Activities to Build Critical Reading Comprehension in EFL Classrooms - Ummi Khaerati Syam; Nunung Anugrawati; Maulina Maulina (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2026)
Reading critically is a fundamental skill to be successful readers. The mental process of reading will work by seeing, analyzing, reviewing, and confirming text and context deeply. Critical reading is the    ideology of the text which follow the critical thinking rules.  The objective of this study was to investigate the effectiveness of Gallery Walk activities in teaching critical reading to the fourth-semester students in Universitas Muhammadiyah Makassar. This study employed a pre-experimental research design to measure the effectiveness of Gallery Walk activities in improving students’ critical reading comprehension. Pre-tests and post-tests were administered to collect the data, which were then analysed using quantitative methods. The primary instrument used in this research was a critical reading comprehension achievement test designed to measure three components of critical reading skills. The findings of the study indicated that students’ critical reading comprehension prior to the implementation of Gallery Walk activities was at a relatively low level, as indicated by the pre-test mean score of 58.06. After the implementation of the Gallery Walk activities, the students demonstrated a substantial improvement in their critical reading comprehension, with the post-test mean score increasing to 86.94. Furthermore, the paired-samples t-test analysis showed a statistically significant difference between the pre-test and post-test scores (t = 25.044, p < 0.05), indicating that the implementation of Gallery Walk activities significantly built students’ critical reading comprehension in the EFL classroom. The implementation of Gallery Walk activities enhances students’ critical thinking skills through active participation in joyful and meaningful learning processes